Impact of Dietary Factors on Thyroid Function and Disorders - Maksymilian Czarnota; Maria Wojcieszek; Dominika Gacka; Aleksandra Żołnierek; Katarzyna Gondek; Magdalena Fidelis; Aleksandra Mączyńska; Wiktoria Szumlińska; Noor Al-karawi; Paulina Kędziorek; Zuzanna Tanç (Journal of Education, Health and Sport)
Thyroid health is intricately linked to nutritional status, as multiple micronutrients and dietary components modulate hormone biosynthesis, metabolism, and immune function. The increasing global prevalence of autoimmune thyroid disorders, particularly Hashimoto’s thyroiditis and Graves’ disease, underscores the need to examine the influence of modifiable dietary factors on thyroid pathophysiology. This narrative review aimed to evaluate current evidence on the role of nutrition—especially micronutrients such as iodine, selenium, iron, zinc, and vitamin D—in thyroid function and autoimmunity. A structured literature search was conducted using PubMed and Scopus to identify relevant human studies published between January 2002 and March 2025. A total of forty-one peer-reviewed articles were selected based on predefined inclusion criteria and assessed for scientific rigor and relevance. The evidence confirms the critical involvement of iodine and selenium in thyroid hormone synthesis and immune modulation, while iron and zinc were found to support enzymatic activity and endocrine stability. Vitamin D emerged as a potential immunoregulatory agent in autoimmune thyroid disease. Furthermore, certain macronutrients—including high-quality proteins, fiber, and omega-3 fatty acids—as well as dietary patterns such as the Mediterranean diet, were associated with favorable thyroid outcomes. Conversely, the intake of goitrogenic foods and soy isoflavones may necessitate caution in predisposed individuals. These findings highlight the relevance of individualized, evidence-based nutritional strategies as adjunctive approaches in the prevention and clinical management of thyroid disorders.